Critical Zone Storage Controls on the Water Ages of Ecohydrological Outputs. Issue 16 (13th August 2020) - Kuppel, S.; Tetzlaff, D.; Maneta, M. P.; Soulsby, C.
Abstract: Spatially explicit knowledge of the origins of water resources for ecosystems and rivers is challenging when using tracer data alone. We use simulations from a spatially distributed model calibrated by extensive ecohydrological data sets in a small, energy‐limited catchment, where hillslope‐riparian dynamics are broadly representative of humid boreal headwater catchments that are experiencing rapid environmental transition. We hypothesize that in addition to wetness status, landscape heterogeneity modulates the water pathways that sustain ecosystem function and streamflows. Simulations show that catchment storage inversely controls stream water ages year‐round, but only during the drier seasons for transpiration and soil evaporation. The ages of these evaporative outputs depend much less on wetness status in the oft‐saturated riparian soils than on the freely draining hillslopes that subsidize them. This work highlights the need to consider local dynamics and time‐changing lateral heterogeneities when interpreting the ages, and thus the vulnerability, of water resources feeding streams and ecosystems in landscapes. Plain Language Summary: Knowing how much time water spends in a landscape (its "age") helps understanding how water travels through it. These dynamics inform of the stability of water resources for ecosystems and societies, and of their vulnerabilities under climate and land use changes. Water ages may vary depending on how wet or dry a location gets between seasons and years. We thus need to learn more about the demographics ("how much and how old?") of the water used by plants, evaporated from soils, and flowing in streams, but it is often impossible to monitor the heterogeneity of water pathways within landscapes. Addressing this challenge, we used a numerical model built upon coupling ecohydrological processes and that maps landscape locations. We adjusted this model using multiple data sets in a catchment representative of humid boreal environments where climate and vegetation are rapidly changing. We found markedly different aging patterns between water escaping the system through the plants, soils, and stream, depending on water storage status. This changing duration of water movement also differs between the catchment as a whole and its parts. This method can be used to better understand the multiple ways in which water moves through landscapes, in current and future conditions. Key Points: Age since precipitation displays inverse storage effect in stream, but not transpiration and soil evaporation, in a humid northern catchment Hysteresis between storage and the age of transpired water suggests cross‐season carryover, despite weak hydroclimatic seasonality Downslope water subsidies result in valley bottom having weaker storage‐age relationships than seen in freely draining hillslopes